Chronic critical illness: the price of survival. (9th November 2015) - Marchioni, Alessandro; Fantini, Riccardo; Antenora, Federico; Clini, Enrico; Fabbri, Leonardo
Abstract: Background: The evolution of the techniques used in the intensive care setting over the past decades has led on one side to better survival rates in patients with acute conditions and severely impaired vital functions. On the other side, it has resulted in a growing number of patients who survive an acute event, but who then become dependent on one or more life support techniques. Such patients are called chronically critically ill patients. Materials & Methods: No absolute definition of the disease is currently available, although most patients are characterized by the need for prolonged mechanical ventilation. Mortality rates are still high even after dismissal from intensive care unit (ICU) and transfer to specialized rehabilitation care settings. Results: In recent years, some studies have tried to clarify the pathophysiological characteristics underlying chronic critical illness (CCI), a disease that is also characterized by severe endocrine and inflammatory impairments, partly accounting for the almost constant set of symptoms. Discussion: Currently, no specific treatment is available. However, a strategic early therapeutic approach on ICU admission might try to prevent the progress of the acute disease towards chronic critical illness.